Petroleum refining: in nontechnical language - Leffler, William L. (Leffler, William L, 2008)
William Leffler's Petroleum Refining in Nontechnical Language, Fourth Edition is designed to give the reader an overview of key refining topics by using relevant analogies, easy-to-understand graphs, formulas, and illustrations. New to this edition is important information on the nature of crude oil and raw materials and a comprehensive discussion on what sets crude oil and oil products price differentials. Also new is a chapter on lubricants as well as the latest technologies employed by refiners. Each chapter was carefully written in nontechnical language to give the reader a basic understanding of the refining industry. The book can be used for self-study, as a classroom textbook, or as a quick reference.
Keywords: Petróleo